(3GdeUahaGJ hGdeMOOGJ (B/s - (3GdYRGhj, QMje jhfS cQhs ((3YeGf(B: s (3OGQ OLdI(B, s, 2008)
(3jJCda gPG GdcJGH hGdPj gh ef SdSdI Gdefgd aj GdQjGVjGJ , ef KdGKI aUhd jTed cd aUd Ydi CeKdI hJeGQjf eJfhYI GdaUd GdChd OQGSI GdeUahaGJ hNhGUgG GdLHQjI hGSJNOGegG aj Md HYV GdeYGOdGJ GdNWjI , hGdaUd GdKGfj jJYdb HGdeMOOGJ GdPj YQV ajg NhGU GdeMOOGJ hQJHI GdeUahaI , CeG GdaUd GdKGdK ajYGdL Md GdeYGOdGJ GdNWjI hWQb MdgG hHYV NhGUgG hbOq CYWi gPG GdcJGH GdcKjQ ef GdJeGQjf CjVGs
(3HjHdjhZQGajG U(B.173s
Keywords: (3GdLHQs; (3GdQjGVjGJs; (3GdeMOOGJs; (3GdeUahaGJs